Pengaruh Variasi Ukuran Bola Baja pada Proses Dry Shot Peening terhadap Mikrostruktur dan Kekerasan Material Implan AISI 316L - Pramudia, Mirza; Romadhon, Ahmad Sahru (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
AISI 316L is a type of 316 austenitic stainless steel with characteristic very low carbon content. This material contains several elements such as molybdenum-chromium-nickel which are aimed to improve the corrosion and oxidation resistances at high temperature applications. The low carbon content and the high level of corrosion resistance of AISI 316L allow this material to be applied to the surgical implant applications in the human body as well as on the welding applications. Several methods of surface treatment applied in AISI 316L are aimed to improve the mechanical properties and corrosion resistance. Dry shot peening is one of cold deformation processes which is conducted on the material surface to improve the mechanical strength. The process was performed by firing balls of steel with particular sizes of 0.5 mm, 1 mm, 2 mm, and 3 mm on specimens with a certain speed that comes from the pressure of the air compressor. The results show that parameter of shot angle at the dry shoot peening process has an influence on microstructure and hardness of the AISI 316L austenitic stainless steel. The highest value of hardness was achieved using 3 mm diameter of steel ball with the value of hardness reached 560 VHN on metal surface then gradually decreased as the depth increased.